Technology of obtaining and investigation of chemical composition of dense extract of hawthorn fruits - Sydora, Natalia; Zuikina, Svitlana; Kovaleva, Alla; Vyshnevska, Liliia (ScienceRise: Pharmaceutical Science, 2018)
In the pharmaceutical market of Ukraine, liquid dosage forms of hawthorn are present and used in complex treatment of cardiovascular diseases. Ukrainian flora has more than 30 species of hawthorns, among which there are unofficial species of wild and cultural species with sufficient raw material base. Aim. To develop a technology for obtaining of dense fruit extracts of unofficial hawthorn species and to determine the chemical composition of the obtained extracts. Methods. For determination of BAS dense of hawthorn fruit extracts was used spectrophotometric method and the method of high performance liquid chromatography (HPLC). Results. The technological scheme of obtaining dense extracts of hawthorn fruit was developed. The content of amino acids, flavonoids and hydroxycinnamic acids was established in густих extracts of fruits C. prunifolia Sarg., С. pseudokyrtostilla Klok. and С. leiomonogyna Klok.. The content of flavonoids ranged from 4.27 % ±0.01 to 10.94 % ± 0.10; hydroxycinnamic acids - from 1.45 % ± 0.02 to 2.56 % ± 0.10. By used the HPLC method in all extracts was detected rutin, chlorogenic and ferulic acids. In dense extract of C. prunifolia Sarg. fruits apigenin-7-O-rhamnoside was identified; С. pseudokyrtostilla Klok. and С. leiomonogyna Klok. - apigenin-7-O-glycoside, apigenin, luteolin; С. leiomonogyna Klok.- luteolin-7-O-diglycoside and quercetin. Conclusions. Dense fruit extracts of C. prunifolia Sarg., С. pseudokyrtostilla Klok. and С. leiomonogyna Klok. were obtained. For the first time, the HPLC method in extracts has determined the content of flavonoids and hydroxycinnamic acids. A comparative study of the amino acid composition of the extracts was carried out